2012
DOI: 10.1016/j.dhjo.2012.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and depression in middle and older-aged adults with multiple sclerosis

Abstract: Background Depression is common among people with multiple sclerosis (MS), and research shows that individuals, including individuals with MS, who are more physically active report lower rates of depression. However, little is known about the relative importance of level of physical activity (e.g., moderate versus vigorous) in relationship to depression, or the role that age might play in this relationship among people with MS. The current study sought to (1) clarify the associations between moderate and vigor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Participants who indicated that five or more symptoms were present more than half the days were considered to have a probable MDE diagnosis. The PHQ–9 is a commonly used measure in the study of persons with MS, having been used recently to assess prevalence of depression (Sjonnesen et al, 2012) and the association of depression with factors such as physical activity (Jensen, Molton, Gertz, Bombardier, & Rosenberg, 2012), fatigue (Amtmann, Bamer, Noonan, et al, 2012), and self-efficacy (Amtmann, Bamer, Cook, et al, 2012). Although there is overlap in symptoms between MS and depression, validation of the PHQ–9 in persons with MS suggests that the measure does not need to be altered to measure depression in persons with MS (Sjonnesen et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Participants who indicated that five or more symptoms were present more than half the days were considered to have a probable MDE diagnosis. The PHQ–9 is a commonly used measure in the study of persons with MS, having been used recently to assess prevalence of depression (Sjonnesen et al, 2012) and the association of depression with factors such as physical activity (Jensen, Molton, Gertz, Bombardier, & Rosenberg, 2012), fatigue (Amtmann, Bamer, Noonan, et al, 2012), and self-efficacy (Amtmann, Bamer, Cook, et al, 2012). Although there is overlap in symptoms between MS and depression, validation of the PHQ–9 in persons with MS suggests that the measure does not need to be altered to measure depression in persons with MS (Sjonnesen et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…However, studies in MS patients have shown that depressive symptoms represent a barrier towards participation in exercise programs . Nonetheless, cross‐sectional studies have provided evidence of an association between physical activity and depressive symptoms in persons with MS . Consequently, data from longitudinal studies evaluating the effects of exercise on MDD and depressive symptoms in MS patients are of potentially high clinical value.…”
Section: Introductionmentioning
confidence: 99%
“…Given that persons with physical disabilities can experience substantial individual and environmental barriers to engaging in physical activity (Williams, Smith, & Papathomas, 2014), these individuals can find it challenging to meet recommended levels of physical activity for general health maintenance and promotion (Rocchi et al, 2017). Accordingly, emerging observational evidence shows negative associations between physical activity quantity and depressive or anxious symptom severity in persons with long-term physical disabilities (Jensen, Molton, Gertz, Bombardier, & Rosenberg, 2012; Stroud & Minahan, 2009; Suh, Motl, & Mohr, 2010; Tawashy, Eng, Lin, Tang, & Hung, 2009).…”
mentioning
confidence: 99%
“…One study of adults with depression found that acute bouts of light, moderate, and hard exercise each produced the same levels of short-term improvements in depressed mood, suggesting the acute affective benefits of physical activity may not necessarily be influenced by the degree of intensity (Meyer, Koltyn, Stegner, Kim, & Cook, 2016). A cross-sectional study of adults with multiple sclerosis (MS) found that moderate physical activity was associated with reduced depression severity, and that quantity of strenuous physical activity was inversely associated with depression in middle-aged adults (45–64 years), but not younger (<45 years) or older (>64 years) age groups (Jensen et al, 2012). A meta-analysis of both observational and interventional research evaluating the relationship between physical activity and negative affect (anxiety and depression) found mixed evidence concerning the extent to which physical activity intensity played a significant role, with observational studies tending to favor vigorous-intensity physical activity, and interventional work finding comparable effects, regardless of intensity (Teychenne et al, 2008).…”
mentioning
confidence: 99%